Diseño e implementación de un prototipo de audífono para obtener el espectro de frecuencias audibles a un oído humano - López Chango, Pamela Alexandra (2017)
The present technical project is aimed at people who have some kind of hearing impairment and who need to improve their condition, is a system that allows the spectrum of audible frequencies to be obtained to a human ear through a prototype of a personalized hearing aid. Analyzed a tonal audiometry that allows us to know the most frequent frequencies that the ear captures, determining the degree of hearing loss that it possesses and based on these data, an optimal design was developed that provides a person with a disability to improve their condition. The prototype is composed of a frequency generator that allows you to measure the minimum thresholds of hearing and by a conditioner of the same signal that allows to improve the hearing increasing the level of intensity of each frequency that the individual needs, O Audiogram in which it is Evidence the hearing loss of each ear, respectively, with these data can determine if the deterioration of the hearing is progressive. To carry out the design of this project, the technical and physical characteristics were analyzed, obtaining a portable product, manageable, and in general allow to compensate the hearing deficiencies of an individual, thus improving their quality of life.